Lessicologia provenzale. II. «Cazual» nella trattatistica (Carte Romanze, 2022)
This short essay analyzes employ and means of the adjective cazual, ‘supplied with cases, declinable’, as technical term in Provençal grammatical trea- tises, where it is used for bicasual declension system. It appears in 14th century and it is used above all in the Leys d’Amors, from which their epigones take it back (also in Catalan treatises).
Keywords: Provençal lexicon; cazual; Provençal declension; grammatical treatises; Leys d’Amors